Examining the decreasing share of renewable energy amid growing thermal capacity: The case of South America. (March 2020) - Arango-Aramburo, S.; Ríos-Ocampo, J.P.; Larsen, E.R.
Abstract: Concerns about climate change have required energy policy to be reconsidered around the world. The transition from fossil fuels to renewable energy has the potential to contribute significantly to the goals of the Paris Agreement (2015), particularly in the developing world. The recent evolution of total installed capacity of electricity mix in eight South American countries and the current renewable energy policy is considered. Indications of an energy paradox are seen: the installed share of thermal capacity increases as energy demand grows, decreasing the share of renewable energy despite the government's stated policy and commitment to increasing renewables in electricity generation through incentives and regulations. The share of installed hydro compared to thermal generation declined from 2007 to 2017 in Chile, Peru, Brazil, Argentina and Bolivia. Furthermore, South American countries are unlikely to reach the aforementioned share of renewables in the energy matrix, with the exception of Uruguay. Thus, organic growth of renewables may not be enough in a region with high potential and a long history of low emissions from electricity. It may be necessary for governments to more actively prioritize, regulate, and support inclusive subsidies for both public and private investors in the electricity sector to reduce the risk of climate change and achieve greenhouse gas reduction goals. Highlights: Installed share of thermal capacity rises as energy demand grows in South America. Renewable generation's investment is limited despite the government's stated policy. South American countries will not reach their renewable targets in the energy market. Organic growth of renewables may not be enough in a region with high potential. Governments must be more active in promoting renewables energy.